Hubungan antara Gaya Mengajar Guru dan Efikasi Diri Siswa dengan Motivasi Belajar Siswa Sekolah Dasar - Gamilina, Pranciska; Noor, Muhammad (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2026)
This study is grounded in the limited number of comprehensive quantitative investigations that simultaneously analyze the relationships between teachers’ teaching styles and students’ self-efficacy and learning motivation in primary education institutions. The study aims to: (1) examine the correlation between teachers’ teaching styles and learning motivation; (2) examine the correlation between students’ self-efficacy and learning motivation; (3) determine the simultaneous relationship of teachers’ teaching styles and students’ self-efficacy with learning motivation; and (4–5) assess the partial relationships of each independent variable with learning motivation after controlling for the other variable. This correlational quantitative research was conducted at SDN Sungai Raya 1 from September to November 2025, involving 63 students in Grades 4–6 selected through total sampling. Data were collected using Likert-scale questionnaires and analyzed through prerequisite tests (normality, linearity, and multicollinearity), Pearson correlation, multiple linear regression, and first-order partial correlation with SPSS 25. The results indicate that the data are normally distributed, the relationships among variables are linear, and no multicollinearity is present. Correlational analysis shows that teachers’ teaching styles are positively and significantly associated with learning motivation (r = 0.524; p = 0.000), as is students’ self-efficacy (r = 0.522; p = 0.000). Simultaneously, both variables explain 36.7% of the variance in learning motivation (R² = 0.367; Sig. F = 0.000). First-order partial correlation analysis controlling for the other predictor confirms significant contributions, with partial r for teachers’ teaching styles (X1) = 0.359 (p = 0.004) and partial r for students’ self-efficacy (X2) = 0.355 (p = 0.005). These findings demonstrate that teachers’ teaching styles and students’ self-efficacy, both individually and jointly, make significant contributions to students’ learning motivation at SDN Sungai Raya 1. The practical implications highlight the importance of pedagogical training for teachers and interventions to strengthen students’ self-efficacy, and recommend further research that incorporates additional external variables to develop a more comprehensive model of learning motivation in the context of primary schools.